Penerapan Dinamika Fluida dalam Perhitungan Kecepatan Aliran dan Perolehan Minyak di Reservoir - Kusumastuti, Dwi Listriana (ComTech: Computer, Mathematics and Engineering Applications, 2014)
Water, oil and gas inside the earth are stored in the pores of the reservoir rock. In the world of petroleum industry, calculation of volume of the oil that can be recovered from the reservoir is something important to do. This calculation involves the calculation of the velocity of fluid flow by utilizing the principles and formulas provided by the Fluid Dynamics. The formula is usually applied to the fluid flow passing through a well defined control volume, for example: cylinder, curved pipe, straight pipes with different diameters at the input and output, and so forth. However, because of reservoir rock, as the fluid flow medium, has a wide variety of possible forms of the control volumes, hence, calculation of the velocity of the fluid flow is becoming difficult as it would involve calculations of fluid flow velocity for each control volume. This difficulties is mainly caused by the fact that these control volumes, that existed in the rock, cannot be well defined. This paper will describe a method for calculating this fluid flow velocity of the control volume, which consists of a combination of laboratory measurements and the use of some theories in the Fluid Dynamics. This method has been proofed can be used for calculating fluid flow velocity as well as oil recovery in reservoir rocks, with fairly good accuration.